University Students Perception of Acceptance and Rejection (Global Journal of Human-Social Science, 2012)
The purpose of this study was to extend the existing body of knowledge on the perception of acceptance and rejection among the university students A conceptual framework which illustrates three dimensions of acceptance and rejection including parental siblings and peer group was developed The present research was a descriptive study which used an indigenous research inventory to measure acceptance and rejection The study was carried out on a sample of 100 university students and it explored the impact of demographic variables including gender age birth order and family income level on determining the level of acceptance and rejection Result of the study revealed that the phenomenon of university students acceptance and rejection does exist among Male students experience higher parental and siblings rejection than females Students from higher income families experience higher rejection compared to students from low income families The findings also indicated that different demographic variables contribute significantly in determining the perceived level of acceptance and rejection
Keywords: Parental; siblings and peer group acceptance and rejection; indigenous inventory; university’s students